2018
DOI: 10.1016/j.ppnp.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

New experimental approaches in the search for axion-like particles

Abstract: Axions and other very light axion-like particles appear in many extensions of the Standard Model, and are leading candidates to compose part or all of the missing matter of the Universe. They also appear in models of inflation, dark radiation, or even dark energy, and could solve some long-standing astrophysical anomalies. The physics case of these particles has been considerably developed in recent years, and there are now useful guidelines and powerful motivations to attempt experimental detection. Admittedl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
726
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(752 citation statements)
references
References 566 publications
(778 reference statements)
2
726
1
2
Order By: Relevance
“…Large cavity-magnon couplings lead to a larger range of frequencies and hence axion masses that the experiment can be sensitive to [11]. Thus the USC achieved here would be advantageous for such an experiment to explore a larger range of the, as yet, unknown axion mass parameter space [56].…”
Section: Resultsmentioning
confidence: 95%
“…Large cavity-magnon couplings lead to a larger range of frequencies and hence axion masses that the experiment can be sensitive to [11]. Thus the USC achieved here would be advantageous for such an experiment to explore a larger range of the, as yet, unknown axion mass parameter space [56].…”
Section: Resultsmentioning
confidence: 95%
“…In Fig. 2, we also show the expected reach of the haloscope searches [35,[159][160][161] by ADMX [162][163][164][165] and KLASH [166], which are also going to explore values of the axion mass that are lighter than what has been recently inferred by numerical computations of the dynamics of the PQ field [16][17][18][19]36] in a different cosmological scenario. On a theoretical viewpoint, the results obtained do not depend on the coupling of the QCD axion with the photons [167][168][169][170], which is nonetheless present when considering the experimental setup [171][172][173][174][175][176].…”
Section: Connection To Observablesmentioning
confidence: 85%
“…Light QCD axions that spectate inflation have recently received attention both from the theory perspective [23-27, 29, 30, 34] and from the perspective of detection in proposed and ongoing experiments [35]. In such a scenario, topological defects are washed out by inflation, and considerable additional effort to assess inhomogeneities like axion strings [16,36,37] or axion miniclusters [38][39][40][41][42] is not required.…”
Section: Introductionmentioning
confidence: 99%
“…T χ and β are in principle calculable, but can be left as nuisance parameters in order to account for systematic uncertainties in the calculations. In fact, QCD axions are only one instance of a general class of axion-like particles (ALPs), which could generally result from the breaking of a U (1) symmetry at some scale f a , with mass generation occurring via the explicit breaking of the residual symmetry at some lower scale Λ [354][355][356]. It can be shown that in a Friedmann-Robertson-Walker-Lemaître universe, a QCD axion or ALP field θ(t) = a(t)/f a satisfies the equation of motion…”
Section: Axions 331 Axion Models and Their Implementation In Gambitmentioning
confidence: 99%